Assessment of Lipid Profile and Electrocardiographic Patterns in Newly Detected Hypothyroid Patients: A Cross-Sectional Analysis in a Tertiary Care Center - Sree, Kolli Laasya; Rao, V. R. Mohan; Sai Vignesh , Challa Venkata; Aishwariyaa, Vinayak Mani (Journal of Neonatal Surgery, 2025)
Background: Hypothyroidism, a condition marked by reduced thyroid hormone levels, can impact various organ systems, including the cardiovascular system, due to metabolic slowdown. This research is proposed to evaluate the lipid profile and correlate cardiac symptoms and changes in ECG and Echo in patients recently diagnosed with hypothyroidism, emphasizing the associated cardiovascular risk factors. Methods: A cross-sectional study was carried out at Chettinad Hospital and Research Institute in Kelambakkam, Chennai, over a period of three months, involving 120 patients who were newly diagnosed with hypothyroidism. Patients underwent evaluations including ECG, echocardiography, and lipid profile. Systemic examination, TSH levels, and relevant exclusion criteria were applied to assess the cardiovascular impact of hypothyroidism. Results: Most patients were aged between 31 and 40 years, with females comprising a significant 81.7% of the group. Commonly reported symptoms included an increase in body weight (79.2%), fatigue (65.8%), dry skin (61.7%), and a hoarse voice (53.3%). Bradycardia was detected in 41.7% of electrocardiograms, while 30.8% showed normal results. Echocardiographic findings revelaed pericardial effusion in 26.7% of the cases, and diastolic dysfunction was observed in 26.7%, predominantly classified as mild. The analysis of lipid profiles indicated increased concentrations of total cholesterol, LDL, VLDL, and triglycerides, along with a reduction in HDL, especially among patients with elevated TSH levels (greater than 10). Conclusion: This research, involving 120 patients recently diagnosed with hypothyroidism, emphasizes that bradycardia is the predominant ECG abnormality observed, with low voltage complexes following closely. Additionally, pericardial effusion emerged as the most prevalent finding in echocardiographic assessments, mandating the critical need for hypothyroidism screening in instances of unexplained pericardial effusion. The sample size provided a comprehensive view of the cardiovascular and lipid profile abnormalities associated with hypothyroidism. Increased concentrations of total cholesterol, serum triglycerides, and VLDL were noted, whereas LDL levels stayed at the upper threshold of normal despite showing statistical significance, and HDL levels remained unchanged. These results warrant the importance of conducting early assessments for cardiovascular risk in patients with hypothyroidism.